Stability of the Einstein static Universe in the scalar–tensor theory of gravity. (13th October 2016) - Miao, Haitao; Wu, Puxun; Yu, Hongwei
Abstract: In this paper, we study the viability of a singularity-free emergent scenario in the scalar–tensor theory of gravity by analyzing the stability of the Einstein static (ES) Universe. In order to obtain analytical results, we assume the perfect fluid which fills our Universe to be radiation or pressureless matter. We find that there are no stable ES solutions when scalar perturbations and tensor ones are considered together. Thus, in the scalar–tensor theory of gravity with a normal perfect fluid, such as radiation or pressureless matter, the emergent mechanism cannot be used to avoid the big bang singularity as the Universe cannot stay at the ES state past-eternally.